Ampliación del rango de distribución del pecho de luna del Marañón (Melanopareia maranonica) en la cuenca media del río Marañón, Perú - Chávez, Cinthia Amelí (2021)
We report documented records of the Marañón Crescentchest (Melanopareia maranonica) in six localities. These have hydrological connectivity with the middle basin of the Marañón River, in the provinces of Celendín (Cajamarca) and Luya (Amazonas), Peru. The records were obtained through occasional encounters, biological evaluations and intensive searches, between 2017 and 2020. These new records are between 1111 and 2074 m in elevation, exceeding its known altitudinal range by more than 1000 m. A total of 39 individuals were registered (11 females, 12 males and 16 indeterminate due to the fact that only auditory registration was made). We expanded the known range with respect to the published records by 121 km in the Cajamarca region and 98.2 km in the Amazonas region. Appropriate habitat for this species is protected in 5,290.12 ha of the Marañón Seasonally Dry Inter-Andean Forest ecosystem and 7,784.67 ha of Andean Scrub, within three Private Conservation Areas and one Regional Conservation Area. These distributional data will help to better understand the distribution of the species and the ecosystems it occupies.